Using the sORFs.Org Database. Issue 1 (28th November 2018) - Olexiouk, Volodimir; Menschaert, Gerben
Abstract: Ribosome profiling involves sequencing of approximately 30‐base‐long stretches of ribosome‐protected mRNA. The technique enables genome‐wide mapping of RNA undergoing active translation. Numerous small open reading frames have been identified by using ribosome profiling, leading researchers to question the assumed non‐functional character of sORFs and to the identification of various important sORF translation products. sORFs.org ( https://www.sorfs.org ) is a public repository of small open reading frames identified by ribosome profiling in a database of over 3 million sORFs across 78 datasets from six species. sORFs.org is a multi‐omics endeavor providing tools and metrics to assess the coding potential of the delineated sORFs. A pipeline is also in place to systematically rescan public mass spectrometry datasets to acquire new experimental evidence for sORF‐encoded polypeptides. sORFs.org provides two distinct query interfaces, export functionality, and various visualization tools to enable inspection of the available information. © 2018 by John Wiley & Sons, Inc.